THE IMPORTANCE OF TREATING THROMBOPHLEBITIS AND CARING FOR PATIENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Thrombophlebitis is a serious medical condition characterized by inflammation of the veins, often caused by impaired blood clotting. This disease is most common in the legs, but it can also develop in other parts of the body. The occurrence and development of thrombophlebitis depends on many factors, among which slow blood circulation, damage to the vein wall, and increased blood clotting ability play an important role. This disease not only reduces the patient's quality of life, but if not treated in a timely and proper manner, it can lead to life-threatening complications, including pulmonary embolism.